Diversity and potential functional role of phyllosphere-associated actinomycetota isolated from cupuassu (Theobroma grandiflorum) leaves: implications for ecosystem dynamics and plant defense strategies - de Matos, Jéssica Pereira; Ribeiro, Dilson Fagundes; da Silva, Ana Karla; de Paula, Camila Henriques; Cordeiro, Isabella Ferreira; Lemes, Camila Gracyelle de Carvalho; Sanchez, Angélica Bianchini; Rocha, Lorrana Cachuite Mendes; Garcia, Camila Carrião Machado; Almeida, Nalvo F.; Alves, Rafael Moyses; de Abreu, Vinicius A. C.; et al. (Springer Nature, 2024)
Exploring the intricate relationships between plants and their resident microorganisms is crucial not only for developing new methods to improve disease resistance and crop yields but also for understanding their co-evolutionary dynamics. Our research delves into the role of the phyllosphere-associated microbiome, especially Actinomycetota species, in enhancing pathogen resistance in Theobroma grandiflorum, or cupuassu, an agriculturally valuable Amazonian fruit tree vulnerable to witches’ broom disease caused by Moniliophthora perniciosa. While breeding resistant cupuassu genotypes is a possible solution, the capacity of the Actinomycetota phylum to produce beneficial metabolites offers an alternative approach yet to be explored in this context. Utilizing advanced long-read sequencing and metagenomic analysis, we examined Actinomycetota from the phyllosphere of a disease-resistant cupuassu genotype, identifying 11 Metagenome-Assembled Genomes across eight genera. Our comparative genomic analysis uncovered 54 Biosynthetic Gene Clusters related to antitumor, antimicrobial, and plant growth-promoting activities, alongside cutinases and type VII secretion system-associated genes. These results indicate the potential of phyllosphere-associated Actinomycetota in cupuassu for inducing resistance or antagonism against pathogens. By integrating our genomic discoveries with the existing knowledge of cupuassu’s defense mechanisms, we developed a model hypothesizing the synergistic or antagonistic interactions between plant and identified Actinomycetota during plant-pathogen interactions. This model offers a framework for understanding the intricate dynamics of microbial influence on plant health. In conclusion, this study underscores the significance of the phyllosphere microbiome, particularly Actinomycetota, in the broader context of harnessing microbial interactions for plant health. These findings offer valuable insights for enhancing agricultural productivity and sustainability.
Keywords: Comparative genomics; Cupuassu; Natural products; Phyllosphere; Plant-microbe-pathogen-interactions; Secondary metabolites